Identification of specific sources of airborne particles emitted from within a complex industrial (steelworks) site. (June 2018) - Beddows, D.C.S.; Harrison, Roy M.
Abstract: A case study is provided of the development and application of methods to identify and quantify specific sources of emissions from within a large complex industrial site. Methods include directional analysis of concentrations, chemical source tracers and correlations with gaseous emissions. Extensive measurements of PM10, PM2.5, trace gases, particulate elements and single particle mass spectra were made at sites around the Port Talbot steelworks in 2012. By using wind direction data in conjunction with real-time or hourly-average pollutant concentration measurements, it has been possible to locate areas within the steelworks associated with enhanced pollutant emissions. Directional analysis highlights the Slag Handling area of the works as the most substantial source of elevated PM10 concentrations during the measurement period. Chemical analyses of air sampled from relevant wind directions is consistent with the anticipated composition of slags, as are single particle mass spectra. Elevated concentrations of PM10 are related to inverse distance from the Slag Handling area, and concentrations increase with increased wind speed, consistent with a wind-driven resuspension source. There also appears to be a lesser source associated with Sinter Plant emissions affecting PM10 concentrations at the Fire Station monitoring site. The results are compared with a ME2 study using some of the same data, and shown to give a clearer view of the location and characteristics of emission sources, including fugitive dusts. Highlights: Contributions of a steelworks to PM mass are assessed. Directional analysis identifies slag handling as a major source. Wind-driven resuspension generates coarse particles. Chemical composition at upwind and downwind sites defines sources. Correlation of PM with SO2 is due to a process emission source.